Maska i labirynt. O procesie indywiduacji zbiorowej w Amarcord Federica Felliniego - Tomczyk-Jarzyna, Izabela (Załącznik Kulturoznawczy, 2022)
The article focuses on selected aspects of Amacord’s film and tries to answer the question why the characters of Fellini’s film were unable to meet their shadow and complete the process of individuation (as defined by C.G. Jung), and whether the diagnosis made by the director with regard to his characters indicates an opportunity, so that the viewer could avoid such blindness. Searching for answers to these questions, I use the anthropological category of labyrinth and mask. I agree with the way of perceiving and defining the concept of fascism proposed by Nicola Chiaromonte.